Konstruksi Makna Pesan dalam Teks Berita Pemberitaan Covid-19 di Kompas.com - Bonaventura Paskaris Kusuma Aji; Turnomo Rahardjo (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2022)
This research tries to understand the meaning of Covid-19 news on Kompas.com by using qualitative research methods and using the narrative theory of the actan model developed by Algirdas Greimas. This research refers to the narrative text of the news collected through the online media Kompas. com during the surge in Covid-19 cases on July 15, 2021. The results of this study found the meaning structure of the Covid-19 news on Kompas.com led to the government that always invites the public to be vigilant. and be vigilant in dealing with the Covid-19 pandemic. The government invites the public to collaborate in all efforts to reduce the spread of Covid-19 which is narrated clearly, straightforwardly, and easily understood by readers.